Photoacclimation in three species of freshwater red algae - Bautista, Anna I. N.; Necchi Júnior, Orlando (FapUNIFESP (SciELO), 2007)
Three freshwater Rhodophyta species (Audouinella eugenea, A. hermannii and Compsopogon coeruleus) were tested as to their responses (photosynthesis, growth and pigment concentration) to two irradiances (low light, LL, 65 μmol m -2 s-1 and high light, HL, 300 μmol m-2 s-1) and two periods (short time, ST, 4 d, and long time, LT, 28 d). Higher growth rates were consistently observed at LL but significant differences were observed only for A. hermannii. Higher values of photoinhibition at LL were found for the three species, which is consistent with the dynamic photoinhibition as a reversible photoprotective mechanism against high irradiance. Light-induced decreases of effective quantum yield (EQY) were observed in the three species consisting of pronounced decreases from LL to HL. Rapid increases of non-photochemical quenching (NPQ) were observed mainly at LL, indicating energy dissipation by reaction centers. Results revealed distinct photoacclimation strategies to deal with high irradiances: the two Audouinella species had only characteristics of shade-adapted algae: acclimation by changes of size of photosy stem units (PSU) under LT and by PSU number under ST; higher values of the photoinhibition parameter (β) and NPQ, and lower values of EQY at LL; higher recovery capacity of potential quantum yield (PQY) at LL and under ST; highly significant positive correlation of electron transport rate (ETR) with NPQ. In addition, C. coeruleus mixed some characteristics of sun-adapted algae: acclimation by changes of PSU number under LT and by PSU size under ST; higher recovery capacity of EQY than the other two species; weak or no correlation of ETR with NPQ. Thus, these characteristics indicate that C. coeruleus cope with high irradiances more efficiently than the Audouinella species.
Keywords: Chlorophyll fluorescence; Growth; Irradiance; Photosynthesis; Pigment; Red algae; algae; Audouinella; Audouinella hermannii; Compsopogon caeruleus; Rhodophyta